Islamic Republic of Mauritania : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2011)
Mauritania's poverty reduction strategy paper is based on a broadly participatory process and serves as the policy framework for the country's economic and social policies. The focus is to accelerate economic growth and stabilize the macroeconomic framework, which benefits the poor, ensure the development of human resources and expansion of basic services, and improve governance and build capacity. In the revision the focus is to strengthen leadership, monitoring, evaluation, and coordination. Mauritania has to take up major challenges to achieve the objectives established at the outset.